Soil Stabilization using Waste Cotton Clothes Coated with Bitumen - Prathamesh Wagare; Shubham Sutar; Shruthi Virapannanavar (International Journal of Engineering and Management Research, 2021)
Properties of soil can be enhanced by using different stabilization techniques. Cotton clothes have a high tensile Strength as compare to natural fibers. In this study waste cotton clothes coated with bitumen were used for stabilization of soil. As waste cotton clothes are cost effective and eco-friendly, they can be modified and used as effective reinforcement material/stabilizer. Experiment was carried out by adding 1% and 2% of waste cotton cloth coated with bitumen to improve its strength characteristics.